Temperature‐dependent lipid metabolism in the blow fly Lucilia sericata. Issue 3 (10th March 2015) - MUNTZER, A.; MONTAGNE, C.; ELLSE, L.; WALL, R.
Abstract An understanding of how arthropods use energy is fundamental to explaining their diverse life histories and adaptation to specific environments. It is also of importance when attempting to predict the impacts of environmental change on patterns of development and phenology. Here, lipid use by the economically important agent of ovine myiasis, Lucilia sericata (Diptera: Calliphoridae), was quantified at a range of temperatures. During pupation, at temperatures above the minimum temperature required for development (9 °C), pupae depleted an average of 30% of their total lipid over the course of pupation regardless of temperature. There was no detectable loss of lipid during pupation at temperatures below 9 °C. In general, larger individuals had the same relative amounts of lipid as smaller individuals. Newly emerged adults metabolized about 16% of the lipid reserves with which they emerged in the first 24 h during flight‐related activity. Starved adults, with access to water but without sucrose or protein, depleted their lipid reserves and died within about 4 days of emergence. However, adults with access to protein and/or carbohydrate were able to maintain a stored lipid content of about 2.38% of their total body mass for at least 14 days after emergence, irrespective of sex. This finding is similar to that in field‐caught individuals, in which lipid content was found to be a mean of 3% of body mass. The data suggest that warmer environmental conditions, within the temperature limits tested here, although shortening the time required for development and altering the patterns of seasonal abundance of L. sericata, are unlikely to impact on fly survival because of greater metabolic demands during non‐feeding stages of the lifecycle.